Previous judicial detection and paedophilic sexual interest partially predict psychological distress in a non-forensic sample of help-seeking men feeling inclined to sexually offend against children. Issue 3 (2nd September 2017) - Konrad, Anna; Haag, Silvia; Scherner, Gerold; Amelung, Till; Beier, Klaus M.
ABSTRACT: Little is known about overall psychological distress in paedophiles who are not formally involved with the criminal justice system. Since knowledge in this context could help to optimise intervention efforts, this study aimed to examine the association between distress as measured with the Brief Symptom Inventory (BSI) and preference- and offence-related variables in a sample of N  = 455 men self-reporting sexual interest in children, of whom 402 were diagnosed as paedophiles. Results showed that 59% reported clinically relevant levels of distress, with paedophiles being significantly more distressed than teleiophiles. A regression analysis revealed that a paedophilic preference and prior detection were relevant predictors for distress. However, past offending behaviour had no impact and the major part of variance could not be explained. The results suggest that paedophilia is associated with distress, but other factors influence whether a paedophilic man is distressed on a clinically significant level.